Contract management of Dhaka city neighborhood upgrading project on physical progress tracking by Microsoft project software - Ashrafuzzaman, Md. (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2023.